The first mammalian aldehyde oxidase crystal structure: Insights into substrate specificity - Coelho, Catarina (2019)
This work was supported by the Portuguese Science and Technology Foundation (FCT-MCTES) through Project PTDC/BIA-PRO/118377/2010 and Grant SFRH/BD/37948/2007(to C. C.) and by the Cluster of Excellence "Unifying Concepts in Catalysis" (to S. L. and M. M.) coordinated by the Technische Universitat Berlin and funded by the Deutsche Forschungsgemeinschaft. The exchange of researchers among laboratories was funded by the DAAD-GRICES program (to M. J. R. and S. L.). The work was also supported by grants from the Associazione Italiana per la Ricerca controil Cancro(AIRC), the Fondazione Italo Monzino, and the Negri-Weizmann Foundation (to E. G.).